Enterpreneur Sebagai Motivasi Meningkatkan Hasil Belajar Akhlak Terpuji - mukhlishotin choiri (Jurnal Pendidikan : Riset dan Konseptual, 2020)
Abstract: The important role of education in preparing the next generation will be more mature and perfect when equipped with skills / skills that can become the character of an educated soul. Through entrepreneurs or who are often known as entrepreneurs is an attitude that prioritizes skills / skills that are integrated with science, innovative creative hard work. Where is the condition of entrepreneurs here as motivation for students to learn the subjects of Aqeedah Akhlaq on morality material praised with more enthusiasm. This is done not because of a sudden but because of the results of learning in the classroom that is less satisfactory so that there is a thought to get a better atmosphere and results. The idea arises where educated people still get knowledge, be creative and get material income, although not much, but they can inspire students in subsequent behavior both for themselves and their families. So that the purpose of this observation as one solution to saturation in the classroom so that it will turn into preoccupation and comfort in learning the Morals through tasks that sell as motivation that moves the heart to continue to learn and try to meet the target of not only academic assessment but really well embedded the character of students who are preneurs or students who have knowledge, who have a hard work ethic, are creative, want to produce innovative and have a good character in every day behavior both in their own conditions and in the midst of the wider community. And thank God, even though the initial data did not meet the target (only 59%), it was very far from the KKM which was 80%, but ended up very satisfying because it exceeded the existing Minimum Completion Criteria (KKM) of 93.1%. Keywords : Entrepreneur, Motivation and Honorable Morals